MITIGATE BANK RISK: SOME REVIEW - Zaman, Hasan (American International Journal of Multidisciplinary Scientific Research, 2020)
Its goal and intent is to examine the structure of capital adequacy, whether or not regulatory regulation is complied with and how shocks from financial and economic stress can be absorbed by the bank’s prescription.